Can the school failure be formative? A study to investigate the educational effectiveness of the summer exams - Parmigiani, Davide; Marsic, Cecilia; Nicchia, Elisabetta; Russo, Cecilia (Formazione & insegnamento, 2019)
The students of the upper secondary schools can have poor grades in one or more subjects at the end of the school year. If so, they have to attend summer courses and face exams either at the end of August or beginning of September. The department of Education at University of Genoa carried out a 2-year research aimed at investigating the educational relevance of those paths. The purposes of this study were: calculating the number of students and the frequency of subjects with poor grades; examining the critical aspects related to these exams (economical, organisational, emotional, etc.); focusing the summative and formative factors supported or not by these assessment tests. During the first year, we conducted a probing study aimed at creating a reliable research instrument whilst, during the second year, the questionnaire was administered to 900 students, 150 teachers and 150 parents from 5 upper secondary schools. The findings indicate several difficulties connected to these exams. In particular, we noticed limits concerning the economical, organisational and formative aspects.